The impact of E-Commerce on business value from SME perspective / Nora Mohd Halid and Nur Farihah Muhammad Yunus - Mohd Halid, Nora; Nur Farihah (Faculty of Business and Management, 2013)
Electronic Commerce (E-Commerce) is a potentially growing business for today's market. It becomes popular medium among companies and individual who operate their business especially among small and medium enterprise (SME).This research study on three dimensions that influence the impact of E-Commerce on business value from SME perspective which are operational efficiency, market efficiency and network efficiency. And the most influence factor is market efficiency. The expatriates of this research is among people who involve with SME and use E-commerce in their business. Data is collect through a questionnaire distributed to 80 expatriates who work for SME companies. Result of the present study showed that the significant correlation relationship between the factors of the impact of E-commerce on business value and the impact of E-commerce on business value. This study also used regression in order to identify which factor is most significant and influence the impact of E-commerce on business value.